2019
DOI: 10.1101/585653
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ZBTB33 (Kaiso) methylated binding sites are associated with primed heterochromatin

Abstract: Background: ZBTB33, also known as Kaiso, is a member of the zinc finger and BTB/POZ family. In contrast to many transcription factors, ZBTB33 has the ability to bind both a sequence-specific consensus and methylated DNA. Although these dual binding preferences enable ZBTB33 to function as an active as well as repressive regulator of gene expression, little is known about the underlining molecular mechanisms. Results: In this study, we aimed to investigate the role of ZBTB33 as a methylated DNA binding factor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…Our results represent, to our knowledge, the largest resource for exploring the in vivo effect of methylation on TF binding: only a handful of studies have previously investigated methylation preferences of a limited number of TFs in vivo while accounting for changes in DNA accessibility. Our results match what has been reported in these studies [2,4,9,10,16], but also reveals a substantial number of novel TFs that are affected by CpG methylation. Of particular interest, our study revealed a significant number of methyl-plus TFs consistent with in vitro studies [5], in stark contrast to previous methods that have attempted to infer the effect of DNA methylation on TF binding [12][13][14][15].…”
Section: Discussionsupporting
confidence: 91%
“…Our results represent, to our knowledge, the largest resource for exploring the in vivo effect of methylation on TF binding: only a handful of studies have previously investigated methylation preferences of a limited number of TFs in vivo while accounting for changes in DNA accessibility. Our results match what has been reported in these studies [2,4,9,10,16], but also reveals a substantial number of novel TFs that are affected by CpG methylation. Of particular interest, our study revealed a significant number of methyl-plus TFs consistent with in vitro studies [5], in stark contrast to previous methods that have attempted to infer the effect of DNA methylation on TF binding [12][13][14][15].…”
Section: Discussionsupporting
confidence: 91%
“…According to ENCODE standard, the experiment will be ideal if both rescue and self-consistency ratios were <2, but it is acceptable that if one value is <2 and the other is more than 2. Previous study about ZBTB33 ChIP-seq used K562 (human erythroleukemic cell line) replicates with self-consistency = 1.37 and rescue ratio = 2.32 for subsequent analyses ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…These enriched factors were reported to play important roles in the respective lineages. For instance, ZBTB33 is specifically important for K562 by binding to methylated DNA, whereas its depletion causes differentiation defects (Cofre et al 2012;Lin et al 2019). GATA1 is a master TF of erythropoiesis with specific expression in myeloid lineage but not in the lymphoblastic leukemia cells (Lee et al 2017;Gutiérrez et al 2020).…”
Section: Cell Type-specific Programs Revealed By Astar-seqmentioning
confidence: 99%